Product differentiation and entry timing in a continuous time spatial competition model - Takeshi Ebina; Noriaki Matsushima; Daisuke Shimizu (Osaka University, Institute of Social and Economic Research (ISER), 2014)
We extend the well-known spatial competition model (d'Aspremont et al., 1979) to a continuous time model in which two firms compete in each instance. Our focus is on the entry timing decisions of firms and their optimal locations. We demonstrate that the leader has an incentive to locate closer to the centre to delay the follower's entry, leading to a non-maximum differentiation outcome. We also investigate how exogenous parameters affect the leader's location and firms' values and, in particular, numerically show that the profit of the leader changes non-monotonically with an increase in the transport cost parameter.
Keywords: L13; R32; C72; 330; Location; Hotelling model; Continuous time; Entry timing